Dinâmica microbiana e aspectos físicos e químicos de café conilon (Coffea canephora Pierre ex Froehner) cultivado em diferentes ambientes e processado por via natural - Pereira, Priscila Vargas (2018)
Microorganisms are present in the different stages of coffee processing and contribute to the final quality of the beverage. The coffee microbiota may vary according to geographic changes, cultivated variety and altitude of the growing site. Knowledge about this microbiota is important especially when starter cultures are to be applied during the drying process in order to improve the quality of the beverage. The aim of this work was to evaluate the microbial diversity present in natural conilon coffee grown at different altitudes and shade, in order to study the relationship of these factors on the present microbiota and their impact on the physical and chemical characteristics of grains. Conilon coffee of two altitudes (300 and 600 m) and two shade (Sunny and Norway) were used.The coffees were dried in suspented plataforme up to 18% moisture and were collected during a fermentation/drying. For the period were transferred to an artificial effect at 45 °C until moisture of 11%. Acidity, pH, soluble solids, ash, phenolics, proteins, lipids, carbohydrates, fiber and moisture were required in coffee fruits. During fermentation by microorganisms were identified by Matrix Assisted Laser Desorption Ionization-Flight Time (MALDI-TOF) and sequencing. Sugars and organics acid were found and quantified by High Performance Liquid Chromatography (HPLC). In the roasted coffee, volatile compounds were identified by gas chromatography coupled to mass spectrometry (GC-MS). An interaction between altitude and face exposure to the sun influenced pH, solubility, ash and phenolic variables of coffee fruits. The same context was not observed for the content of lipids, proteins, carbohydrates, fiber and moisture. The main genera of microorganisms were Pichia, Candida, Meyerozyma, Bacillus and Staphylococcus. Acetic acid and succinic acid during the fermentation process. A concentration of sucrose, fructose and glucose varied between samples throughout the fermentation. Composed of half a dozen toasts, having the same effect in relation to the altitude and face of sun exposure. The evaluation of the microbiota present in conilon coffees allows different heights and faces of exposure to the sun is important for the knowledge of microbial species present during natural processing in Brazil, since these studies are scarce in the scientific literature.